Manufacturing Information and Data Systems : Analysis, Design and Practice. - Cecelja, Franjo (Elsevier, 2002)
Recent years have witnessed an increase in the use of information technology in manufacturing, so much so that it has rapidly permeated the organization at every level. Consequently, there is a growing need for those related to or interested in manufacturing to understand the nature of this technology and the way it can best be used to increase competitive advantage, hence the profit. This book is a contribution towards better understanding of information technology and information systems and their application in manufacturing. The main feature of this book is that it addresses information sy.
Keywords: Manufacturing processes -- Data processing.; Industrialists -- Information resources management.; Industrial management -- Data processing.; Management information systems.; elektronické knihy; electronic books